A Brief Comparative Analysis of Two Bilingual Dictionaries of Islamic Finance and Economy - Ali, Antar Fuad; Shunmugam, Krishnavanie; Saleh, Abdulmajid Obaid Hasan (Journal of Modern Languages, 2021)
With the growth of Islamic banking and new research into Islamic economy, the need to investigate related Islamic terms in these fields has become very important for concerned bodies. To date, there has not been adequate research to shed light on bilingual dictionaries on Islamic finance and economy. Two bilingual dictionaries (Arabic –English) that have a substantial number of entries on Islamic finance and economy terms (IFETs) are Mu’jam Lughat Al Fuqahā’ (‘Dictionary of Islamic Legal Terminology’) (1988) and ISRA Compendium for Islamic Finance Terms (2010). The current paper aims to provide a brief comparative analysis of some salient aspects with regard to the introductory matter, main content and appendixes of these two specialized, bilingual dictionaries. It also attempts to investigate whether a certain set of randomly selected IFETs are included in the two selected dictionaries to generally gauge the extent of the semantic content of these dictionaries. For those involved in work related to Islamic finance and economy like translators, researchers, students and other professionals in the field, the analysis here will bring to awareness the extent of the usefulness of these two dictionaries by highlighting their merits and demerits. The study concludes by making recommendations for improvements that can be made to future bilingual dictionary publications dealing with IFETs.